Microbial Profile and Antibiotic Susceptibility Pattern of Frozen Food in India - Bi Bi Zainab Mazhari; Fehaid Alanazi; Khalid Abosalif; Tagwa Salah Ahmed Mohammed Ali; Sanaa Elfaith Hussein; Dayanand Agsar (Journal of Pure and Applied Microbiology, 2024)
This investigation was carried out to examine the safety and microbiological quality of products made from meat, dairy and vegetables. Samples of frozen food were examined for the presence of Gram-negative bacteria. A total of 49 frozen food samples were collected, including chicken nuggets, chicken fillets, chicken sticks, breaded breast chicken, fish, beef burger and minced beef roll, white cheese, camembert cheese, and vegetables (okra and green peas). Standard methods were used to determine the diversity of bacterial isolates in various food samples. About 182 isolates of Escherichia coli, 63 isolates of Salmonella typhi, 51 isolates of Pseudomonas, and 63 isolates of Klebsiella were recovered from the various frozen food samples. Meat samples showed a high prevalence of E. coli and Pseudomonas. The antibiotic susceptibility patterns of the isolated bacterial strains were also examined. Out of 12 antibiotics, only ciprofloxacin and ofloxacin showed a high level of susceptibility. According to the study’s findings, the majority of the frozen meat product samples contained a significant number of bacteria and were therefore unsafe for human consumption. These microorganisms can cause infection and are therefore associated with a high risk to the consumers. Therefore, it is important to pay attention to health and education issues in relation to food safety.